Synthesis and in vitro evaluation of 4-substituted furano[3, 2-c] tetrahydroquinolines as potential anti-cancer agents. (2nd September 2016) - Chen, Can; Zingales, Sarah; Wang, Ting; Yuan, Mingyong; Wang, Dan; Cai, Lulu; Jiang, Qinglin
Abstract: A convenient and mild method for the synthesis of substituted furano [3, 2-c]tetrahydroquinoline derivatives was developed, using the multi-component Povarov reaction. Of the synthesized tetrahydroquinoline derivatives, compound10a displayed the greatest cellular proliferation inhibitory activities with IC50 values of 2.5–16.7 μmol/l. In addition, 10a induced murine C6 glioma cell apoptosis in a dose-dependent manner by up-regulating the expression of Bax, caspase-3, and caspase-9, and by down-regulating Bcl-2. Our findings suggest that these novel compounds have potential as therapeutic agents via inducing mitochondrial apoptosis.